MIGRATION MEXICO – UNITED STATES: DIMENSIONS AND PERSPECTIVES - Roberto Zepeda; Jorge Virchez; Alfonso Marquina Marquez (EtnoAntropoZum, 2016)
Migration flows in the Americas have expanded in the last decades, especially from Central and South America to North America. The Americas comprise the largest flows of migration worldwide. While Mexico is the largest exporter of migrants, the United States becomes the largest receptor of migrants in the world. Most of the contemporary migration towards the United States is undocumented and clandestine generating risks for both the migrants and the recipient country as the border becomes porous. Migration flows respond mainly to economic factors, geographic proximity and the wage-related disparities between the United States and Latin American countries. The solution to these problems requires cooperation between the expeller and receiver countries through a multilateral agreement that regulates the flows of migrants to meet the demands of labour force in the United States, especially in the agricultural sector and the low-paid services sector.